Exposure to particulate pollutant increases the risk of hospitalizations for Sjögren’s syndrome - Zhang, Tian-Ping; Dou, Jing; Wang, Li; Wang, Shan; Wang, Ping; Zhou, Xiao-Hui; Yang, Chun-Mei; Li, Xiao-Mei (Frontiers in Immunology, 2022)
Numerous researches have reported the role of air pollution in the development of autoimmune diseases. However, few have evaluated the relationship between inhalable particulate matter (PM) exposure and Sjögren's syndrome (SS). This study aimed to analyze the association between exposure to two particulate pollutants (PM2.5, PM10) and SS-related hospitalizations. Daily data were obtained on PM2.5 and PM10, meteorological factors, and hospital hospitalizations for SS between 2016 and 2021. The daily data on PM2.5 and PM10, meteorological factors, and the number of SS hospitalizations were collected between 2016 and 2021. A distributed lag non-linear model and a generalized linear model were established to explore the association between PM2.5 and PM10 exposure and hospitalizations for SS. Stratified analyses were performed to explore possible gender-, age-, and season-related differences in PM2.5 and PM10 effects. Exposure to PM2.5 was related to the evaluated risk of hospitalizations for SS (RR=1.015, 95% CI: 1.001-1.029, lag 3 day), similarly, PM10 exposure had a statistically significant positive association with SS hospitalizations (RR =1.013, 95% CI: 1.001-1.026, lag 3 day). Stratified analyses found that exposure to PM2.5 and PM10 exhibited higher impact on SS-related hospitalizations in female patients and exposure to PM2.5 was also associated with the higher risk of SS-related hospitalizations in patients aged ≥ 65 years. In addition, exposure to PM2.5, PM10 in colder season were more likely to increase SS-related hospitalizations. Our findings suggested that exposure to PM2.5 and PM10 were significantly linked to an elevated risk of hospitalizations for SS.